Microsponges: a breakthrough tool in pharmaceutical research - Abhishek Tiwari; Varsha Tiwari; Binita Palaria; Manish Kumar; Deepak Kaushik (SpringerOpen, 2022)
Abstract Background A microsponge delivery system (MDS) is an innovative and unique way of delivering drugs in a structured manner. Using microsponge drug delivery, regulated drug delivery may now be achieved quickly and easily. Main body MDS comprises porous microspheres ranging in size from 5 to 300 microns, with a large porous structure and a very tiny spherical shape. MDS is normally used to deliver drugs via topical channels, but they have recently shown the potential approach to drug delivery via oral, ophthalmic and parenteral routes. MDS can easily modify the pharmaceutical release contour and improve formulation stability while minimising the negative impact of the drug. The fundamental purpose of microsponge drug administration is to reach the highest possible peak plasma concentration in the blood. The capacity of MDS to self-sterilise is their most prominent attribute. Conclusions MDS is used as anti-allergic, anti-mutagenic and non-irritant in innumerable investigations. This review includes formulation, criteria for drugs to be incorporated in MDS, formulation methods, assessment parameters, and role of MDS in the management of various disorders. This review will be quite useful in the future in exploring the MDS in different disorders. Graphical Abstract